Performance, functionalism and form in á»Šzá» n oral poety - Armstrong, Imomotimi (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
Since the publication of Ruth Finnegan's influential Oral Literature in Africa, way back in 1970, scholars have been paying earnest attention to oral traditions on the African continent. That seminal book pointed out to Africanist scholars the need to urgently collect and document the oral literatures of their various ethnic groups before they die out. However, it is the verbal arts of the major ethnic groups on the continent that very often benefit from this collection and documentation, as it were. Therefore, this study sought to examine the oral poetry of the á»Šzá» n, a minority ethnic nationality, located in the oil-rich Niger Delta region of Nigeria. The study employed unstructured interviews and participant observations to collect the data for the research. The transcribed and translated data was examined through three eclectic theories to the study of folklore: Russian formalism, performance and functionalism. The study found out that á»Šzá» n oral poetry is a combination of songs and one person's praise chants. Moreover, it revealed that praise chanting is a recent practice amongst the á»Šzá» n that was introduced into á»Šzá» nland by Chief Adolphus Munamuna from the Yoruba of southwestern Nigeria. Furthermore, the study established that oral poetry plays important roles amongst the people. Besides, it ascertained that the performance of some sub-categories of the poetry is highly dramatic and theatrical. It also discovered that stylistic techniques such as formula, parallelism, proverb, ideophone, praise title, metaphor, repetition, alliteration, assonance, vowel lengthening, amongst others, give the poetry the quality of "literariness." In addition, the study found out that the poetry, like oral poetry in other ethnic groups, demonstrates the three qualities of change, adaptability and survival. The study has contributed to existing scholarship on African oral traditions in the sense of collecting, documenting and generating awareness on á»Šzá» n oral poetry, most importantly pointing out the existence of praise chanting amongst a people who had no such culture and the conditions that gave rise to that practice.
Keywords: Ijo (African people; Ijo language; Folk poetry, Ijo; Folk poetry -- Nigeria